2014
DOI: 10.1016/j.cell.2014.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Resistance to a Last-Resort Antibiotic in Staphylococcus aureus via Bacterial Competition

Abstract: Antibiotic resistance is a key medical concern, with antibiotic use likely being an important cause. However, here we describe an alternative route to clinically relevant antibiotic resistance that occurs solely due to competitive interactions among bacterial cells. We consistently observe that isolates of Methicillin-resistant Staphylococcus aureus diversify spontaneously into two distinct, sequentially arising strains. The first evolved strain outgrows the parent strain via secretion of surfactants and a tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
166
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(172 citation statements)
references
References 160 publications
5
166
0
1
Order By: Relevance
“…This study shows that cooperator-cheat interpretations of clinical observations can be warranted, such as those in the recent study by Köhler et al (28), which suggested that P. aeruginosa quorum sensing (QS) mutants in acute lung infections arise as cheats and not because QS is redundant in the lung. Furthermore, an intriguing experimental demonstration of the potential clinical relevance of microbial social interactions comes from the work by Koch et al (29), which showed that intraspecific competition can select for antibiotic-resistant Staphylococcus aureus bacteria in the absence of antibiotic pressure. Together with studies on cooperator-cheat dynamics in natural populations of bacteria, such as iron acquisition of Vibrio in seawater (30) and toxin production in Bacillus infecting moth larvae (31), this finding calls for a reevaluation of how we interpret evolutionary change of natural microbial populations.…”
Section: Social Interactions Drive Selection On Pyoverdine Metabolismmentioning
confidence: 99%
“…This study shows that cooperator-cheat interpretations of clinical observations can be warranted, such as those in the recent study by Köhler et al (28), which suggested that P. aeruginosa quorum sensing (QS) mutants in acute lung infections arise as cheats and not because QS is redundant in the lung. Furthermore, an intriguing experimental demonstration of the potential clinical relevance of microbial social interactions comes from the work by Koch et al (29), which showed that intraspecific competition can select for antibiotic-resistant Staphylococcus aureus bacteria in the absence of antibiotic pressure. Together with studies on cooperator-cheat dynamics in natural populations of bacteria, such as iron acquisition of Vibrio in seawater (30) and toxin production in Bacillus infecting moth larvae (31), this finding calls for a reevaluation of how we interpret evolutionary change of natural microbial populations.…”
Section: Social Interactions Drive Selection On Pyoverdine Metabolismmentioning
confidence: 99%
“…Additionally, coupling selection in the within-host environment with selection occurring outside the host can provide a more accurate understanding of how variation in virulence is maintained in nature [94,95]. Within-host competition has also explained why some forms of methicillin-resistant Staphylococcus aureus (MRSA) do not respond to treatment with vancomycin [96]. Unlike other cases where antibiotic resistance occurs after antibiotic treatment or due to high levels of resistance circulating in the community, some forms of vancomycin resistance in MRSA appear to occur due to within-host competition.…”
Section: Implications Of Within-host Competition To Host Healthmentioning
confidence: 99%
“…Due to large population sizes coupled with short generation times, bacterial adaptation can be observed in a course of days or months, allowing for its experimental investigation (Kawecki et al 2012;Rosenzweig and Sherlock 2014;Martin et al 2016). Experimental evolution studies continuously deepen our understanding of microbial adaptation, revealing common evolutionary scenarios such as genome reduction (Nilsson et al 2005) or genome rearrangements (Martin et al 2017), hypermutability (Flynn et al 2016;Tenaillon et al 2016), or diversification (Rainey and Travisano 1998;Poltak and Cooper 2011;Koch et al 2014;Flynn et al 2016;Kim, Levy and Foster 2016). The last one, where microbes diversify into distinct variants (typically referred to as morphotypes as they are identified based on distinct colony morphology), appears to be very common, especially in structured environments which offer alternative niches varying in nutrient and oxygen content (Martin et al 2016;Steenackers et al 2016).…”
Section: Introductionmentioning
confidence: 99%